Intramuscular stimulation vs sham needling for the treatment of chronic midportion Achilles tendinopathy: A randomized controlled clinical trial - Solomons, Lyndal (PLoS One, 2020)
BACKGROUND: The insertion of filiform needles intramuscularly (a.k.a. intramuscular stimulation/dry needling) has been suggested as a possible treatment for various painful musculoskeletal conditions. Our aim was to answer the question, is intramuscular stimulation more effective than sham intramuscular stimulation/dry needling for the treatment of Achilles tendinopathy? METHODS: 52 participants with persistent midportion Achilles tendinopathy began and 46 completed one of three treatment protocols which were randomly assigned: (G3) a 12-week rehabilitation program of progressive tendon loading plus intramuscular stimulation (n = 25), (G2) the same rehabilitation program but with sham intramuscular stimulation (n = 19), or (G1) a reference group of rehabilitation program alone (as an additional control) (n = 8). The a priori primary outcome measure was change in VISA-A score at 12 weeks–VISA-A was also measured at 6 weeks, and at 6 and 12 months. Secondary outcome measures include the proportion of patients who rated themselves as much or very much improved (%), dorsiflexion range of motion (degrees), and tendon thickness (mm). RESULTS: The study retention was 94% at 12 weeks and 88% at 1 year. VISA-A score improved in all three groups over time (p<0.0001), with no significant difference among the three groups in VISA-A score at the start of the study (mean ± SD: G3 59 ± 13, G2 57 ± 17, G1 56 ± 22), at 12 weeks (G3 76 ± 14, G2 76 ± 15, G1 82 ± 11) or at any other timepoint. The percentage of patients who rated themselves as much or very much improved (i.e. treatment success) was not different after 12 weeks (G3 70%, G2 89%, G1 86% p = 0.94), or at 26 (p = 0.62) or 52 weeks (p = 0.71). No clinically significant effects of intervention group were observed in any of the secondary outcome measures. CONCLUSION: The addition of intramuscular stimulation to standard rehabilitation for Achilles tendinopathy did not result in any improvement over the expected clinical benefit achieved with exercise-based rehabilitation alone.